Significant Reduction of Pulmonary Embolism in Orthopaedic Trauma Patients. Issue 2 (February 2019) - Starr, Adam J.; Shirley, Zachary; Sutphin, Patrick D.; Sanders, Drew; Eastman, Alexander; Au, Brigham; Sathy, Ashoke; Hu, Gene; Gebrelul, Aaron; Minei, Joseph; Cripps, Michael W.
Abstract : Objectives: To report results of a protocol to lessen incidence of pulmonary embolism (PE) among orthopaedic trauma patients. Design: Retrospective review. Setting: Level 1 trauma center. Patient/Participants: Orthopaedic trauma inpatients were included in the study. Intervention: On arrival, an orthopaedic trauma patient's PE risk is calculated using a previously developed tool. If possible, patients at high risk are given their first dose of enoxaparin before leaving the emergency room. If other injuries preclude enoxaparin, then chemoprophylaxis is held for 24 hours. Twenty-four hours after arrival, the patient's ability to receive enoxaparin is reassessed. If possible, enoxaparin is started, with dosing twice a day. If enoxaparin is still contraindicated, a removable inferior vena cava filter is placed. Adequacy of enoxaparin dosing is tested using anti-factor Xa assay, drawn 4 hours after the third dose of enoxaparin. If the anti-factor Xa result is less than 0.2 IU/mL, a removable inferior vena cava filter is placed. If the result is 0.2–0.5 IU/mL, enoxaparin dosing is continued. If greater than 0.5 IU/mL, the dose of enoxaparin is reduced. Outcome Measure: The main outcome measure was rate of PE. Results: From September 1, 2015 to December 31, 2015, our hospital admitted 420 orthopaedic trauma patients. Fifty-one patients were classed as high risk for PE. In September through December 2015, 9 sustained PE, 1 of which was fatal. From September 1, 2016 to December 31, 2016, our hospital admitted 368 orthopaedic trauma patients with comparable age and Injury Severity Score to 2015. Forty patients were at high risk for PE, 1 sustained a nonfatal PE. PE incidence from September to December 2016 was significantly lower than in 2015 ( P = 0.02). Overall, 26 patients managed under the new protocol had IVCFs placed, 21 had their filters removed, and 3 died with filters in place. There were no complications during filter placement or removal. One patient had hemorrhage felt to be attributable to enoxaparin. Conclusions: Our protocol emphasizes more robust enoxaparin dosing, and more frequent use of IVCF, but only among those at high risk. We lessened the incidence of PE, with a low complication rate. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.